Dynamic thermal simulation of horizontal ground heat exchangers for renewable heating and ventilation of buildings - Gan, Guohui (Elsevier, 2016)
A ground heat exchanger is used to transfer thermal energy stored in soil in order to provide renewable heating, cooling and ventilation of a building. A computer program has been developed for simulation of the dynamic thermal performance of horizontally coupled earth-liquid heat exchanger for a ground source heat pump and earth-air heat exchanger for building ventilation. Neglecting the dynamic interactions between a heat exchanger and environments would significantly over predict its thermal performance and in terms of the amount of daily heat transfer the level of over-prediction could be as much as 463% for an earth-liquid heat exchanger and more than 100% for an earth-air heat exchanger. The daily heat transfer increases with soil moisture and for an earth-liquid heat exchanger the increase is between 3% and 35% with increase in moisture from 0.22 to 0.3 m3/m3 depending on the magnitude of heat transfer. Heat transfer through a plastic earth-liquid heat exchanger can be increased by 10%–12% if its thermal properties are improved to the same as surrounding soil. The increase is smaller between 2% and 4% for an earth-air heat exchanger. In addition, an earth-liquid heat exchanger is more efficient than an earth-air heat exchanger.